Implementasi Investasi Sosial Sektor Industri Pertambangan - Masjon Parhusip; Eddy Winarno; Edy Nursanto (Publikasi Indonesia, 2022)
PT Freeport Indonesia is a mining company which includes mining, processing and exploration of ore containing copper, gold and silver. PT Freeport Indonesia operates in the highlands of Mimika Regency, Papua Province, Indonesia. PT Freeport Indonesia is committed to providing benefits to the community around the operational area, these benefits are realized through various social investment activities carried out with partners. This study aims to provide an overview of PT Freeport Indonesia's commitment in implementing community development and empowerment that has been going on for the last three years. The research method is carried out using qualitative methods in general, describing a research to be simpler and subjective. Data processing was carried out by studying literature using data from the social investment annual report of PT Freeport Indonesia. The results of this study provide a general description of PT Freeport Indonesia's commitment to implementing community development and empowerment in the operational are.